2003
DOI: 10.1021/jo026399m
|View full text |Cite
|
Sign up to set email alerts
|

A Tandem Metal Carbene Cyclization−Cycloaddition Approach to the Pseudolaric Acids

Abstract: An approach toward the synthesis of the antifungal and cytotoxic pseudolaric acids based on the tandem metal carbene cyclization-cycloaddition reaction is described. Using this strategy, the advanced intermediate 3a bearing three of the four stereocenters of the target molecules has been synthesized. The substrate-controlled diastereoselectivity of the tandem carbene cyclization-cycloaddition was preferential for the undesired diastereomer, but reagent control through the use of Hashimoto's chiral rhodium cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…We confirmed that the bromohydrin 20 is reconverted into the starting epoxide 19 upon treatment with a base. Chlorination15 of the bromohydrin 20 and subsequent deprotection of the alcohols protected as MOM ethers afforded the fully functionalized half fragment 21 with a cis tetrahydrofuran ring, as confirmed by the observation of an NOE between the hydrogen atoms indicated in structure 21 .…”
Section: Methodsmentioning
confidence: 75%
“…We confirmed that the bromohydrin 20 is reconverted into the starting epoxide 19 upon treatment with a base. Chlorination15 of the bromohydrin 20 and subsequent deprotection of the alcohols protected as MOM ethers afforded the fully functionalized half fragment 21 with a cis tetrahydrofuran ring, as confirmed by the observation of an NOE between the hydrogen atoms indicated in structure 21 .…”
Section: Methodsmentioning
confidence: 75%
“…After having established a concise route to cyclized compound 4 , it was then converted to tricyclic compound 16 through hydrogenation and reductive ring‐opening using SmI 2 (Scheme ) . After silylation of the resulting secondary alcohol 16 , the Takai reaction was used to introduce an exo ‐methylene moiety, affording compound 18 , whereas the Wittig reaction using Ph 3 P=CH 2 did not proceed.…”
Section: Figurementioning
confidence: 99%
“…4-Dimethylaminopyridine( DMAP) was effective, although the reaction time had to be prolonged to 7h (entry 9). [13] After silylation of the resulting secondary alcohol 16,t he Takai reactionw as used to introduce an exo-methylene moiety, [14] affordingc ompound 18,w hereas the Wittig reaction using Ph 3 P=CH 2 did not proceed. Althought he cyclization with triethylamine gave the desired product in 35 %y ield along with a significant amount of byproduct 13,q uinuclidine and DABCO were effective.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent work, Chiu and co-workers [167,168] have reported an intramolecular 1,3-dipolar cycloaddition approach toward the pseudolaric acids 85, in which the dipolarophile is an unactivated 1,1-disubstituted alkene. Hence, treatment of the diazo ketone 86 with catalytic Rh 2 (OAc) 4 furnished a mixture of tricyclic products 87 and 88 in nearly equal proportions (Scheme 19.13).…”
Section: Natural Product Synthesis and Core Structuresmentioning
confidence: 99%